ENVIRONMENTAL EDUCATION IN INCLUSIVE SCHOOLS - Augusto de Souza Aguiar, Bruno (Journal of Interdisciplinary Debates, 2023)
The purpose of this study was to delve into the environmental perspectives of teachers from the early grades up to the eighth grade at Escola Municipal Padre Antônio Henrique in Recife-PE. The focus was on understanding how these educators perceive the environment and environmental education (EE), and what drives them to discuss environmental topics with their students. The said institution integrates students with special educational needs (such as the deaf-mute) into conventional classes, underscoring the need to recognize the role of EE in the development of these students. To gather data, a semi-structured questionnaire was initially administered, aimed at understanding teachers’ relationship with education and their environmental experiences. From the feedback, a landscape of environmental perspectives and the challenges faced by teachers in promoting EE was drawn. Subsequently, the gathered information was analyzed and represented using graphs and tables. The drawn conclusions sought to provide insights to enhance environmental practices within the school setting. This research is premised on the belief that schools play a pivotal role in the interaction between humans and their environment. The results highlighted the significance of bolstering environmental efforts within schools, which includes sufficient planning time, continuous training for teachers, and resources for hands-on activities. It is hoped that this research will support educators dedicated to environmental education in inclusive settings and spark a review of the pedagogical approaches the school employs in this regard.